Open photoacoustic cell configuration applied to the thermal characterization of liquid CdS nanocomposites - Faraji, Nastaran; Mat Yunus, Wan Mahmood; Kharazmi, Alireza; Saion, Elias; Behzad, Kasra (Springer, 2014)
CdS nanofluids were prepared by the gamma-radiation method at different radiation doses. The samples were characterized by UV–Vis spectroscopy and transmission electron microscopy. The open cell photoacoustic technique was used to measure the thermal effusivity of the CdS nanocomposites. In this technique a He–Ne laser was used as the excitation source and was operated at 632.8 nm with an output power of 70 mW. The precision and accuracy of this technique were initially established by measuring the thermal effusivity of distilled water and ethylene glycol. The thermal-effusivity values of these two samples were found to be close to the values reported in the literature. The thermal effusivity of CdS nanofluids decreased from (0.453 to 0.268) W⋅S1/2⋅cm−2⋅K−1 with increased dosage of gamma radiation.